The Effect of Transformational Leadership on the Organizational Performance in Higher Education Institutions in Iraq - Ahmed Waham, Mohammed; Abdul Rahman, Rafiduraida; Wan Mustaffa, Wan Salmuni (International Business Education Journal, 2020)
Higher education institutions in Iraq faces numerous issues which affected the performance of teaching staff and education quality. Thus, a university needs effective leaders who can inspire the teaching staff and drive transformation in the whole education process. Transformational leaders establish a vision to deliver transformation and change by motivating and inspiring followers. This study aims to identify the influence of transformational leadership on the organisational performance of Iraqi universities. 387 academic staff were sampled from five universities in Iraq and surveyed by using self-administered questionnaire. Structural equation modelling (SEM) and regression analysis were used to analyse the data. The result showed that transformational leadership has a significant effect on organisational performance. Therefore, a university should consider transformational leadership as a critical leadership quality in designing training programs and developing future recruitment policies.